Leveraging Implementation Science for Cardiovascular Health Equity: A Scientific Statement From the American Heart Association - Moise, Nathalie; Cené, Crystal W.; Tabak, Rachel G.; Young, Deborah R.; Mills, Katherine T.; Essien, Utibe R.; Anderson, Cheryl A.M.; Lopez-Jimenez, Francisco (Circulation (New York, N.Y.), 2022)
Reducing cardiovascular disease disparities will require a concerted, focused effort to better adopt evidence-based interventions, in particular, those that address social determinants of health, in historically marginalized populations (ie, communities excluded on the basis of social identifiers like race, ethnicity, and social class and subject to inequitable distribution of social, economic, physical, and psychological resources). Implementation science is centered around stakeholder engagement and, by virtue of its reliance on theoretical frameworks, is custom built for addressing research-to-practice gaps. However, little guidance exists for how best to leverage implementation science to promote cardiovascular health equity. This American Heart Association scientific statement was commissioned to define implementation science with a cardiovascular health equity lens and to evaluate implementation research that targets cardiovascular inequities. We provide a 4-step roadmap and checklist with critical equity considerations for selecting/adapting evidence-based practices, assessing barriers and facilitators to implementation, selecting/using/adapting implementation strategies, and evaluating implementation success. Informed by our roadmap, we examine several organizational, community, policy, and multisetting interventions and implementation strategies developed to reduce cardiovascular disparities. We highlight gaps in implementation science research to date aimed at achieving cardiovascular health equity, including lack of stakeholder engagement, rigorous mixed methods, and equity-informed theoretical frameworks. We provide several key suggestions, including the need for improved conceptualization and inclusion of social and structural determinants of health in implementation science, and the use of adaptive, hybrid effectiveness designs. In addition, we call for more rigorous examination of multilevel interventions and implementation strategies with the greatest potential for reducing both primary and secondary cardiovascular disparities.